2023
DOI: 10.1002/iid3.835
|View full text |Cite
|
Sign up to set email alerts
|

TFRC in cardiomyocytes promotes macrophage infiltration and activation during the process of heart failure through regulating Ccl2 expression mediated by hypoxia inducible factor‐1α

Yanyun Pan,
Jinxiu Yang,
Jin Dai
et al.

Abstract: BackgroundCardiac hypertrophy is an initiating link to Heart failure (HF) which still seriously endangers human health. Transferrin receptor (TFRC), which promotes iron uptake through the transferrin cycle, is essential for cardiac function. However, whether TFRC is involved in the process of pathological cardiac hypertrophy is not clear.MethodsTransverse aortic constriction (TAC) mouse model and mice primary cardiomyocytes treated with isoproterenol (ISO) or phenylephrine (PHE) were used to mimic cardiac hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“… 21 , 22 In addition, TFRC was reported to induce macrophage activation and infiltration through STAT3‐Ccl2 signaling pathway, promoting the development of heart failure. 23 In our study, iron levels were significantly increased in I/R group (6.926 ± 0.3414 vs. 12.52 ± 0.4135; Figures 6C and 7D ), the combination of HID and I/R resulted in significant myocardial damage and cardiac dysfunction. Beyond the high expression of TFRC, it remains to be further investigated whether there are other mechanisms that mediate iron overload.…”
Section: Discussionsupporting
confidence: 52%
“… 21 , 22 In addition, TFRC was reported to induce macrophage activation and infiltration through STAT3‐Ccl2 signaling pathway, promoting the development of heart failure. 23 In our study, iron levels were significantly increased in I/R group (6.926 ± 0.3414 vs. 12.52 ± 0.4135; Figures 6C and 7D ), the combination of HID and I/R resulted in significant myocardial damage and cardiac dysfunction. Beyond the high expression of TFRC, it remains to be further investigated whether there are other mechanisms that mediate iron overload.…”
Section: Discussionsupporting
confidence: 52%
“…CCL2 can promote cardiac decompensation ( 40 ), and upregulation in stressed and injured cardiomyocytes ( 41 ). TFRC in cardiomyocytes recruits and activates macrophages by secreting CCL2 to induce myocardial hypertrophy and promote HF development ( 42 ). Daniela Impellizzeri et al found that pro-inflammatory mediator CCL2 was significantly upregulated in inflammation of the colon and is associated with increased disease activity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%